Single Drug Intervention in Treatment of Amlapitta with special reference to Bhavprakash Samhita (International Journal of Ayurveda and Pharma Research, 2024)
Bhavprakash Samhita deals with detailed description medicinal plants used in treatment of various disorders along with knowledge of other aspects of Ayurveda. Amongst them Acharya Bhavmishra in the Madhyam khanda has elaborated the Amlapitta disease. Bhrihatrayee has scattered description of Amlapitta disease whereas the elaboration of this disorder is explained in Madhav nidan, Kashyap Samhita, Bhavprakash Yogratnakar and Harit Samhita. In Bhavprakash Samhita, Amlapitta is explained along with Shleshmapitta. In both these types, Amlata is Vikruti and vitiated Dosha are Kaphapitta with difference in symptoms as per the dominant Dosha. Other Granthakars have mentioned Kaphapittaj as a type of Amlapitta according to its Dosha predominance. Whereas in Bhavprakash Samhita Shleshmapitta is described as a separate entity. The treatment mentioned in Bhavprakash Samhita comprises of Shodhan and Shaman Chikitsa. In Shaman Chikitsa Acharya Bhavmishra has used Single drugs in various combinations. This article deals with details of Shaman chikitsa and single Dravyas used in it.